The Effect of Market Value and BID–ASK Spread on Stock Holding Period in LQ45 Companies Listed on the Indonesia Stock Exchange for the 2021–2024 Period - Hutagalung, Itce; Arison Nainggolan; Tri Dharma Sipayung; Wesly Andri Simanjuntak (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2026)
This study aims to determine whether market value and bid-ask spread affect the holding period. The population of this study consists of LQ 45 companies listed on the Indonesia Stock Exchange for the period 2021-2024. The population includes 45 companies with the same sample that meets the criteria. The technique used is purposive sampling. The data analysis technique used is multiple linear regression. The results of the study show that partially, the independent variable market value has a significant effect on the stock holding period. The bid-ask spread does not have a significant effect on the stock holding period. Furthermore, simultaneous testing proves that market value and bid-ask spread have a significant effect on the stock holding period. In the coefficient of determination test, it was found that the variables market value and bid-ask spread can explain 83.6% of the holding period variable, while the remaining 16.4% is influenced by other variables outside the research model.